Study on the implementation of suloek at the Darussalam Alwaliyyah Labuhan Haji Islamic boarding school in Aceh - Maqfirah Agus Putri; Fransisca Tassia; Masni (At Turots: Jurnal Pendidikan Islam, 2026)
Sufism is a method of spiritual education aimed at shaping individuals with a deep sense of the divine. Education is not merely about the transfer of knowledge, but also the shaping of character through consistent spiritual practices. Dayah Darussalam Al-Waliyyah in Labuhan Haji implements Sufism through the practice of suloek as a tradition of the Naqshbandi order to draw closer to Allah through dhikr, tawajjuh, and the control of worldly desires. The objective of this study is to understand how Sufi practices are carried out in the suloek tradition in Aceh. The research method employed is ethnography, in which the researcher actively participates in the research process. The findings reveal the presence of Sufi practices within suloek, as the stages of suloek are intrinsically linked to Sufism for instance, the teachings emphasize patience, diligence, and a focus solely on worship. Thus, since the suloek contains elements of Sufism, the study of Sufism is inherent in the practice of the suloek.